Pengukuran User Experience Terhadap Penggunaan Aplikasi SIMVONI dengan Pendekatan Metode HEART - Auralia Miffatul Jannah; Tri Lathif Mardi Suryanto; Arista Pratama (Universitas Bandar Lampung (UBL), 2022)
SIMVONI is an acronym for the Virtual Indonesia Museum Application, which is a museum digitization service in the form of a virtual tour 3600. Every digital service requires feedback from users or visitors to achieve the basic goals of developing the service, not preparation for SIMVONI's efforts to become a digital e-museum in Indonesia. The purpose of this study is to analyze the impact of user experience on using SIMVONI through the website. This study uses a quantitative approach with the HEART method which is analyzed using Importance Performance Analysis (IPA). The number of respondents used for the sampling test is 257 provided that they have visited the SIMVONI page at least once. The results showed that there were 10 of 34 HEART items recommended for improvement (action) on SIMVONI, while the most important factors to get attention for improvement in a quick time were Retention and Engagement.